Numerical study and parametric analysis on performance enhancement of a latent heat storage unit with fractal fins. (30th November 2022) - Li, Wei; Wang, Jing; Zhang, Yuli; Zhang, Xu; Wei, Fan; Zhao, Jun
Abstract: Adding fractal fins is an approach to improve the heat storage performance. In this paper, a new type of fractal fins is established, and a new evaluation index is putting forward in order to analyze the performance of the heat storage unit from the view of temperature uniformity. The advantages of fractal fins and the optimal number of fins are discussed by temperature uniformity factor. Finally, the influence of angle ratio, length ratio and phase change material (PCM) parameters on heat storage units are discussed by dimensionless criterion number. The results show that the application of fractal fins can improve the performance of heat storage unit and the temperature uniformity factor can be reduced by 131.5 % at most. The heat storage unit with six fractal fins has the smallest temperature uniformity factor. The optimal angle ratio and length ratio are 2/3 and 0.5 respectively. The change of PCM parameters has different effects on different melting periods. This research has a further guiding role for the development of fractal finned latent heat storage units. Highlights: Combining fractal fins with latent heat storage, a new model is established. The new model is compared with the traditional straight rib and non-fin. A new evaluation index, temperature uniformity factor ( ε ), is proposed. ε and dimensionless numbers are used to analyze the heat storage performance.